Konstruksi Identitas Remaja dalam Tekanan Sosial pada Novel Argantara Kajian Sosiologi Sastra - Lusyiana Efendy; Ahmad Ilzamul Hikam (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines the construction of adolescent identity in Falistiyana's novel Argantara through a sociological literary approach. Adolescent identity is the result of a process of searching for identity that takes place during the transition to adulthood and is greatly influenced by social factors, such as family, school, peers, and community norms. The Argantara novel depicts the complexity of adolescent life through its characters who experience social pressure in various forms, ranging from family expectations, social competition in the school environment, to stigma against differences in social background. This study found that social pressure is a significant factor in shaping and often limiting the expression of adolescent identity. However, the characters in the novel also show various resistance strategies, such as symbolic rebellion, selective adaptation, and the search for meaning through emotional relationships. Using Erikson's identity theory and Pierre Bourdieu's habitus concept, this study concludes that adolescent identity in Argantara is formed through the dialectic between social structure and individual agency. Literature, in this context, not only reflects the social reality of adolescents, but also becomes a medium to criticize the social pressures faced by the younger generation.